2013
DOI: 10.1371/journal.pone.0063245
|View full text |Cite
|
Sign up to set email alerts
|

DRAM1 Regulates Autophagy Flux through Lysosomes

Abstract: We have previously reported that the mitochondria inhibitor 3-nitropropionic acid (3-NP), induces the expression of DNA damage-regulated autophagy modulator1 (DRAM1) and activation of autophagy in rat striatum. Although the role of DRAM1 in autophagy has been previously characterized, the detailed mechanism by which DRAM1 regulates autophagy activity has not been fully understood. The present study investigated the role of DRAM1 in regulating autophagy flux. In A549 cells expressing wilt-type TP53, 3-NP increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
66
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 37 publications
4
66
0
Order By: Relevance
“…The results also support the involvement of DRAM1 in the degradation of autophagosomes [6]. However, Galavotti et al found that DRAM1 was not involved in starvation-and mTORmediated autophagy activation [7].…”
Section: Dram1 Regulates Autophagy Flux Through Lysosomessupporting
confidence: 72%
See 3 more Smart Citations
“…The results also support the involvement of DRAM1 in the degradation of autophagosomes [6]. However, Galavotti et al found that DRAM1 was not involved in starvation-and mTORmediated autophagy activation [7].…”
Section: Dram1 Regulates Autophagy Flux Through Lysosomessupporting
confidence: 72%
“…Knock-down of DRAM1 resulted in the impairment of lysosomal acidification and the accumulation of LC3-II, indicating reduced autophagy flux [6]. DRAM1 appeared to regulate autophagy in both the early and later stages.…”
Section: Dram1 Regulates Autophagy Flux Through Lysosomesmentioning
confidence: 94%
See 2 more Smart Citations
“…DRAM1 was found to trigger selective autophagy downstream of TLR signaling promoting mycobacterial phagosome maturation, phagolysosome fusion, and anti-mycobacterial activity (33). Knockdown of DRAM1 inhibits the v-ATPase and acidification of lysosomes (51). Thus, it is tempting to speculate that DRAM1 links IFN-γ induction of autophagy, TCIRG1, and acidification of lysosomes.…”
Section: Discussionmentioning
confidence: 99%